Teba modern sebagai solusi lingkungan: Kampanye digital dan kesadaran masyarakat di desa Lebih - Ni Wayan Ditha Sasmitha; Komang Ema Marsitadewi (STAI Auliaurrasyidin Tembilahan, 2025)
This community engagement program aims to enhance the understanding and awareness of residents in Desa Lebih, Gianyar Regency, regarding organic waste management rooted in local wisdom through the implementation of Teba Modern. The program adopts a participatory communication approach that positions community members as active subjects in the educational process. This approach was operationalized through the involvement of residents as talents in the production of an educational video, as well as through a socialization forum and dialogue-based discussion that facilitated two-way communication. These strategies enabled environmental messages to be co-constructed with the community, drawing on their lived experiences and everyday practices, thereby increasing message receptivity. The effectiveness of the program was evaluated using pre-test and post-test instruments administered to 11 respondents. Findings indicate an increase in the average score from 6.4 (“Fair Understanding”) to 11.3 (“Good Understanding”), with all respondents demonstrating improved comprehension. These results suggest that a participatory approach is effective in strengthening organic waste literacy and fostering community readiness to adopt Teba Modern as a sustainable effort to reduce the burden on TPA (final waste disposal sites).